2017
DOI: 10.3329/ajmbr.v3i2.33581
|View full text |Cite
|
Sign up to set email alerts
|

Left oblique laparotomy for caesarean section in a cow due to dystocia

Abstract: Caesarean Section is a surgical procedure in which an incision is given through the abdominal wall and uterus in order to deliver fetus. It is also known as C-section is one of the most challenging surgical procedures in case of dystocia to save fetus live. A 6 years old HF cross breed cow, weighing 300 kg was admitted to the Teaching Veterinary Hospital (TVH), Chittagong Veterinary and Animal Sciences University (CVASU) with a history of prolonged labour pain. At first all the physical examination was done. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In animals, there are few studies on drotaverine despite the fact that there are veterinary products approved without prescription that contain this substance indicated in dogs, cats, horse and cattle: Espa-Vet® (Square Pharmaceuticals Ltd®, Dhaka, Bangladesh); Drotavet® (Romvac®, Ilfov, Romania); Vetalgin® (AVZ Animal Health®, Moscow, Russia). Studies on spasmolytic effect of drotaverine were performed in cows with dystocia [26], vaginal prolaps [27] and in horses with abdominal colic [28]. Other authors suggested stomach emptying inhibition of drotaverine in Beagle dogs [29].…”
Section: Introductionmentioning
confidence: 99%
“…In animals, there are few studies on drotaverine despite the fact that there are veterinary products approved without prescription that contain this substance indicated in dogs, cats, horse and cattle: Espa-Vet® (Square Pharmaceuticals Ltd®, Dhaka, Bangladesh); Drotavet® (Romvac®, Ilfov, Romania); Vetalgin® (AVZ Animal Health®, Moscow, Russia). Studies on spasmolytic effect of drotaverine were performed in cows with dystocia [26], vaginal prolaps [27] and in horses with abdominal colic [28]. Other authors suggested stomach emptying inhibition of drotaverine in Beagle dogs [29].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the major problems in the dairy industry that increases cow and calf mortality, decreases milk yield, delays uterine involution, and reproductive performance, ultimately resulting in substantial financial loss (Yohannes et al., 2018). Among all domestic animals, cattle and buffalo are considered to be the most suspicious species having the highest incidence rate of dystocia (Hasan et al., 2017). In cattle, it can be relieved by different obstetric methods, including the cesarean operation and fetotomy (Ajeel, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Prepartum cervicovaginal prolapse is seen occasionally in cows during advanced pregnancy (Hasan et al 2017). The frequent cause is hormonal followed by dietary and managemental.…”
Section: Introductionmentioning
confidence: 99%